2009
DOI: 10.1002/chem.200901408
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐Assisted Functionalization of Carbon Nanostructures in Ionic Liquids

Abstract: The effect of microwave (MW) irradiation and ionic liquids (IL) on the cycloaddition of azomethine ylides to [60]fullerene has been investigated by screening the reaction protocol with regard to the IL medium composition, the applied MW power, and the simultaneous cooling of the system. [60]Fullerene conversion up to 98 % is achieved in 2-10 min, by using a 1:3 mixture of the IL 1-methyl-3-n-octyl imidazolium tetrafluoroborate ([omim]BF(4)) and o-dichlorobenzene, and an applied power as low as 12 W. The mono- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 55 publications
0
31
0
Order By: Relevance
“…[4] Moreover, CNT/polymer composites and CNT/ionic liquid gels have been considered for the preparation of actuator systems [5] and reaction media. [6] CNTs have been extensively explored for the development of highly sensitive and specific nanoscale biosensors. [2] Due to their intrinsic stability, structural flexibility and high aspect ratio, CNTs may act as highly efficient vehicles for the transport of a wide range of molecules across living cell membranes.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Moreover, CNT/polymer composites and CNT/ionic liquid gels have been considered for the preparation of actuator systems [5] and reaction media. [6] CNTs have been extensively explored for the development of highly sensitive and specific nanoscale biosensors. [2] Due to their intrinsic stability, structural flexibility and high aspect ratio, CNTs may act as highly efficient vehicles for the transport of a wide range of molecules across living cell membranes.…”
Section: Introductionmentioning
confidence: 99%
“…To date, several successful strategies have been applied to covalently derivatize CNTs sidewalls. Typical approaches include acid oxidation [25], cycloadditions spanning from the widely known 1,3-dipolar cycloaddition, namely the Prato reaction [2628] to the Bingel [2 + 1] cyclopropanation [29], radical additions via diazonium salts [3031] grafting of polymers. Nevertheless the creation of novel covalent bonds disrupt the sp 2 network of non-derivatized CNTs and may thus alter their inherent properties [30,32].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al demonstrated a one-pot functionalization of a graphene sheet with porphyrin derivatives using a similar reaction. [49] The cycloaddition of azomethine ylides to fullerene under microwave irradiation was achieved within 10 min with conversion up to 98%. From the results of the luminescence lifetimes of materials, either energy or electron transfer between graphene and the covalently bonded porphyrins occurred after photoexcitation.…”
Section: Cycloaddition Reactionsmentioning
confidence: 99%